Labour Mobility Within the Eu: Major Effects and Implications for the Main Sending and Receiving Economies - Georgiana, Noja Gratiela (European Journal of Economics and Business Studies, 2016)
The paper aims to analyse the effects induced by labour mobility within the European Union, focusing both on emigration and immigration effects for major sending and host economies in terms of the overall economic activity, empowering the business enterprise sector and labour market, as well as on economic (labour force) and non-economic (humanitarian, asylum seekers) migration. Labour mobility within the European Union is an important coordinate of the economic integration process and one of the freedoms granted to the member states, with significant consequences upon their economies. Nevertheless, the international labour migration mainly resides from wage differentials, working conditions or opportunities between sending and host economies, thus proving to be an important symbol of global economic inequality. Taking into consideration all these aspects, our analysis is based on developing various double-log fixed (LSDV) and random (ECM) effects models, using a panel structure that covers five main EU destination countries and ten New EU Member States, respectively a complex set of indicators compiled during 2000-2014 and 2006-2015. The models are processed through OLS and GLS methods of estimation, as well as by using the correlated panels corrected standard errors (PCSE) method, being completed by in-sample and out-of-sample predictions. The results show that immigration flows have important economic consequences leading to significant changes in labour market performances both for natives and foreign population (decreases in employment rates and lowering wage levels). Still, one of the most important positive effects of immigration reflected by the results obtained is represented by an increase in the number of innovative enterprises in the host country, thus confirming the theories linking migration to innovation. In terms of labour emigration, there is evidence to attest that it generates positive effects on the main sending economies from Central and Eastern Europe on the GDP per capita, earnings and exports, especially through remittances, but the overall negative impact is predominant.